Synthesis of Gelatin Methacryloyl Analogs and Their Use in the Fabrication of pH-Responsive Microspheres - Karolina Valente; Geneviève N. Boice; Cameron Polglase; Roman G. Belli; Elaina Bourque; Afzal Suleman; Alexandre Brolo (MDPI AG, 2024)
pH-responsive hydrogels have numerous applications in tissue engineering, drug delivery systems, and diagnostics. Gelatin methacryloyl (GelMA) is a biocompatible, semi-synthetic polymer prepared from gelatin. When combined with aqueous solvents, GelMA forms hydrogels that have extensive applications in biomedical engineering. GelMA can be produced with different degrees of methacryloyl substitution; however, the synthesis of this polymer has not been tuned towards producing selectively modified materials for single-component pH-responsive hydrogels. In this work, we have explored two different synthetic routes targeting different gelatin functional groups (amine, hydroxyl, and/or carboxyl) to produce two GelMA analogs: gelatin A methacryloyl glycerylester (polymer A) and gelatin B methacrylamide (polymer B). Polymers A and B were used to fabricate pH-responsive hydrogel microspheres in a flow-focusing microfluidic device. At neutral pH, polymer A and B microspheres displayed an average diameter of ~40 µm. At pH 6, microspheres from polymer A showed a swelling ratio of 159.1 ± 11.5%, while at pH 10, a 288.6 ± 11.6% swelling ratio was recorded for polymer B particles.